Bahasa Arab Dan Identitas Keagamaan Dalam Kajian Sosiolinguistik - Khasanah, Nginayatul (Universitas Cokroaminoto Yogyakarta, 2024)
This research aims to examine the use of Arabic, both written and spoken, in relation to religious identity in Petanahan, Kebumen. This qualitative descriptive research uses interview techniques, observation and documentation. The conclusion is that the Petanahan village community is a pluralistic and multicultural society with various unique features found. The use of terms such as Rahimahulloh, hafidzohulloh, qodarulloh, tabarokalloh, jazakalloh, 'afwan, akhi, ukhti, ana, antum, abi, umi, differentiates the identity of the village's Muslims who can be grouped into traditional Muslims, traditional-modern Muslims, modern Muslims.